Food expenditure and GST in New Zealand. Issue 2 (3rd May 2016) - Ball, Christopher; Creedy, John; Ryan, Michael
Abstract : This paper investigates the welfare effects on New Zealand households of zero-rating food in a goods and services tax (GST). The detailed effects, for a range of household types, are investigated using Household Economic Survey data. Demand responses to consumer price changes are estimated and welfare changes, in terms of equivalent variations, are obtained. Comparisons are also made across clusters, consisting of groups of households with similar characteristics. A tax change is found to produce a very small amount of progressivity in the GST. Redistribution is from households without children and with high total expenditure to households with children and low total expenditure, and towards older households.